2022
DOI: 10.17275/per.22.4.9.1
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Role of Critical Thinking Disposition in the Relationship between Perceived Problem-Solving Skills and Metacognitive Awareness of Gifted and Talented Students

Abstract: This study aims to examine relationships among critical thinking dispositions, perceived problem-solving skills and metacognitive awareness of gifted and talented students, and to test a structural equation model based on these relationships. The study was conducted using the correlational research design and the study group, which was selected by using convenience sampling method, consisted of 502 gifted and talented students who were registered to Science and Art Centers in Adana, Kayseri and Mersin, Turkey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…This finding in the present study is in line with that reported by Tekkol and Demirle (2018), revealing the high level of self-directed learning skills among Turkish undergraduates across disciplines (Natural sciences, Social sciences, Health sciences, and Fine arts). The same finding was also recorded in the study by Boran and Karakus (2022), involving gifted and talented school students whose high metacognitive awareness significantly affected their problem-solving skills directly displayed in many creative solutions. Similarly, a high level of motivation self-regulation strategies among Yemeni college seniors was uncovered by Alotumi (2021).…”
Section: Discussion and Implicationsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding in the present study is in line with that reported by Tekkol and Demirle (2018), revealing the high level of self-directed learning skills among Turkish undergraduates across disciplines (Natural sciences, Social sciences, Health sciences, and Fine arts). The same finding was also recorded in the study by Boran and Karakus (2022), involving gifted and talented school students whose high metacognitive awareness significantly affected their problem-solving skills directly displayed in many creative solutions. Similarly, a high level of motivation self-regulation strategies among Yemeni college seniors was uncovered by Alotumi (2021).…”
Section: Discussion and Implicationsupporting
confidence: 79%
“…Fisher et al (2001) contains only three subcomponents (self-management, desire for learning subscale, and self-control);Ghanizadeh and Mirzaee (2012) measured the participants' self-regulation using a 32-question scale questionnaire of four subcomponents (planning, self-monitoring, effort, and self-efficacy); Tekkol and Demirle (2018) used a 21-item scale of four sub-dimensions/components (motivation, self-confidence; self-control, and selfmonitoring); while a 20-item scale of four factors was utilized byUztosun (2020) as mentioned above and Yaghi (2021) implemented a 38-item scale of three subcomponents (global strategies, problem solving strategies, and support strategies). Also,Boran and Karakus (2022) used a questionnaire scale of 18 items under only one factor component to measure the participants' metacognitive awareness.…”
mentioning
confidence: 99%
“…Most of the research done was to investigate the self-regulation of high school learners (e.g., Boran and Karakus, 2022), and college and university learners (e.g., Alotumi, 2021;Do, 2022). My present study is aimed at young learners (as defined in chapter 2).…”
Section: Discussionmentioning
confidence: 99%
“…Participants in these studies were nursing students in the second, third, and fourth years of study in this paper, in the third and fourth years in the study done by Kim et al [ 24 ]; and in the first and second grades in the study by Ji et al [ 13 ]. Problem-solving ability can be developed under the influence of various factors; those identified in previous studies include communication ability [ 13 ], critical thinking ability [ 12 , 25 ], metacognition [ 11 ], and self-directed learning [ 2 ]. These factors are continuously improved through various interpersonal relationships formed while learning and studying liberal arts and other major subjects, rather than existing as innate abilities [ 26 ].…”
Section: Discussionmentioning
confidence: 99%